2018
DOI: 10.1088/2057-1976/aad44a
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Total Occlusions using a hydraulic pressure wave: a feasibility study

Abstract: Crossing highly calcified occlusions is technically challenging mainly due to guidewire buckling. In an effort to prevent buckling, a catheter that uses a dynamic impulse load is proposed. The proposed Wave catheter consists of an input plunger to generate an impulse at the handle, a hydraulic pressure wave confined within a Ø2 mm catheter to transfer the impulse towards the tip, and an output plunger to transfer the impulse to the occlusion. To determine the feasibility of this catheter, an experiment was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…There was, however, a discrepancy between the COMSOL modeling results and the actual catheter result with respect to the effect of curvature. In the COMSOL model, as well as our previous study (21), it was found that the curvature of the shaft does not have a significant effect on the efficiency of the system. In our experimental results with the developed catheter, we found that the curvature did have a significant effect.…”
Section: Summary Of Main Findingsmentioning
confidence: 50%
See 4 more Smart Citations
“…There was, however, a discrepancy between the COMSOL modeling results and the actual catheter result with respect to the effect of curvature. In the COMSOL model, as well as our previous study (21), it was found that the curvature of the shaft does not have a significant effect on the efficiency of the system. In our experimental results with the developed catheter, we found that the curvature did have a significant effect.…”
Section: Summary Of Main Findingsmentioning
confidence: 50%
“…The theoretical maximum frequency the Wave catheter can function is equal to the velocity of the pressure wave. In a previous study (21), we found that the fluid travels with an approximated velocity of 550-585 m/s through the catheter. This velocity translates into a maximum frequency of 550 Hz and thus an assumed crossing time of 0.14 s.…”
Section: Summary Of Main Findingsmentioning
confidence: 83%
See 3 more Smart Citations